Link It, Open It, Use It: Changing How Education Data Are Used to Generate Ideas - Rossiter, Jack (Note, 2020)

Link it, open it, use it: changing how education data are used to generate ideas - Rossiter, Jack (Center for Global Development, 2020)

Link It, Open It, Use It: Changing How Education Data Are Used to Generate Ideas - Rossiter, Jack (Note, 2020)

Does Education Need a QALY and Is LAYS It? - Crawfurd, Lee; Hares, Susannah; Le Nestour, Alexis; Rossiter, Jack (Center For Global Development, 2019)

Do High-Stakes Exams Promote Consistent Educational Standards? - Rossiter, Jack; Abreh, Might Kojo; Ali, Aisha; Sandefur, Justin (Working Papers, 2021)
Each year over two million secondary-school students across English-speaking West Africa sit coordinated exams, with the explicit goal of maintaining consistent educational standards across schools and over time. We find that scores across math items drawn from different exam years—when taken by an identical group of students on the same day—closely track fluctuations in Ghana’s national pass rates over time, absent any role for cheating or changes in real performance.

Planning for School Reopening and Recovery After COVID-19: An Evidence Kit for Policymakers - Carvalho, Shelby; Rossiter, Jack; Angrist, Noam; Hares, Susannah; Silverman, Rachel (Center for Global Development, 2020)

Planning for School Reopening and Recovery After COVID-19 - Carvalho, Shelby; Rossiter, Jack; Angrist, Noam; Hares, Susannah; Silverman, Rachel (Center for Global Development, 2020)
Keywords: ⛔ No DOI found